2018
DOI: 10.1634/theoncologist.2017-0621
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Analyzing Circulating Tumor DNA in Patients with Metastatic Colorectal Cancer

Abstract: Multiple genomic changes caused by clonal evolution induced by therapeutic pressure and corresponding intratumoral heterogeneity have posed great challenges for personalized therapy against metastatic colorectal cancer (mCRC) in the past decade. Liquid biopsy has emerged as an excellent molecular diagnostic tool for assessing predominant spatial and temporal intratumoral heterogeneity with minimal invasiveness.Previous studies have revealed that genomic alterations in ,, , and, as well as other cancer-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 87 publications
2
32
0
1
Order By: Relevance
“…However, molecular testing of the RAS gene is extremely limited because tumor tissue is limited, and biopsies are invasive. More recently, some studies suggested that the consistency of liquid biopsy and tumor-tissue biopsy testing was more than 90% in the detection of the RAS gene (25,26). Liquid biopsy is an important method of monitoring RAS mutation status in mCRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular testing of the RAS gene is extremely limited because tumor tissue is limited, and biopsies are invasive. More recently, some studies suggested that the consistency of liquid biopsy and tumor-tissue biopsy testing was more than 90% in the detection of the RAS gene (25,26). Liquid biopsy is an important method of monitoring RAS mutation status in mCRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, these biomarkers are concentrated mainly in histochemistry and molecular biology techniques. Their application is limited to a certain extent because of the high price and need for specific experimental equipment [ 3 , 4 ]. Therefore, it continues to be important to find convenient, effective, and inexpensive prognostic markers for patients with GI malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in cases with newly developed metastatic liver tumors, US‐guided liver biopsy could be an appropriate approach for tissue‐based clinical sequencing. Liquid biopsy could overcome the limitations of tissue‐based analysis due to intra‐ and intertumor heterogeneity, but will require robust validation . In addition, recent evidence revealed the role of cancer–stroma interactions in the development and progression of cancer .…”
Section: Discussionmentioning
confidence: 99%